2020
DOI: 10.1111/hel.12705
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and attitudes regarding Helicobacter pylori infection in Chinese physicians and public population: A national cross‐sectional survey

Abstract: BackgroundThere is a lack of reports on the awareness of Helicobacter pylori (H pylori) prevention and treatment in the general Chinese population. And whether the knowledge level will affect their action toward screening was unknown. This study aimed to conduct a national survey on the knowledge, attitudes, and practice regarding H pylori infection in Chinese physicians and the public.MethodsThis was an Internet‐based survey of the general Chinese population and Chinese physicians from different specialties, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(62 citation statements)
references
References 37 publications
7
48
0
Order By: Relevance
“…This descriptive cross-sectional study compared the knowledge of H. pylori between health science and non-health science undergraduate students in Saudi Arabia and found that the overall level of knowledge was poor among both groups. Our finding of poor knowledge was similar to those reported among physicians and students in a national survey in China [22] and among the healthy population in Korea [24]. A lower level of knowledge (24.6%) was also reported among the general population in the United Arab Emirates (UAE) [25].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This descriptive cross-sectional study compared the knowledge of H. pylori between health science and non-health science undergraduate students in Saudi Arabia and found that the overall level of knowledge was poor among both groups. Our finding of poor knowledge was similar to those reported among physicians and students in a national survey in China [22] and among the healthy population in Korea [24]. A lower level of knowledge (24.6%) was also reported among the general population in the United Arab Emirates (UAE) [25].…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, a large proportion of our respondents reported "reading articles" and "media" as their main sources of information. This may explain why most of the students (76.9%) reported having heard about H. pylori, which is a higher proportion than those reported among Chinese physicians and the general population (49.8%) [22] and those reported in a review of nine studies from China, South Korea, North America, Ethiopia, India, and Malaysia (22-33%). Eight of the nine studies were conducted among the population at risk, except North America, where they were from the general population.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Considering the lack of current tools evaluating H. pylori KAPs, particularly among high-risk populations, a tool was developed by the authors using the World Health Organization Guide to Developing Knowledge, Attitude, and Practice Surveys (WHO, 2008). Additionally, literature and international studies were used for further guidance on how to structure the questionnaire (Canbaz, Sunter, Peksen and Leblebicioglu, 2005) (Ahmed, Salih, Jafri, Ali Shah and Hamid, 2009) (Abebaw et al, 2014) (Tsongo et al, 2015) (Driscoll et al, 2017) (Cano-Contreras et al, 2018) (Wu et al, 2020). The questionnaire was developed in English then translated to Arabic.…”
Section: Questionnaire Designmentioning
confidence: 99%
“… 13 14 Such opportunistic screening is performed on a voluntary basis, based on an individual or physician’s request. 14 The screening rate for HP in China (21.7%) is far from satisfactory, 15 and the general population’s lack of awareness of HP risk factors or symptoms and negative attitude towards screening contribute to delays in diagnosis. 11 …”
Section: Introductionmentioning
confidence: 99%